COST AND VOLUME IN THE MILK PASTEURIZING INDUSTRY. - Wasserman, Max J. (The Accounting Review, 1946)
The relationships between costs and volume of output have long constituted an important segment of business policy, accounting, and economic theory, specially in the U.S. Analyses of these relationships are utilized in value, price, and distribution theory as well as in business policy development and economic planning. In spite of the importance of these relationships, few actual data are publicly available for studying them since the materials must be derived from a detailed analysis of the books of account of industry. In a world of private business, such data are not commonly available for publication. The Agricultural Adjustment Administration, in 1933, obtained under oath and in sufficient detail for cost and output analysis, the balance sheets and operating cost statements of a representative group of milk pasteurizers and distributors operating in thirty-five important milk markets. These financial statements, which were obtained in view of the preparation of milk-marketing agreements, were audited and expressed in a standard form by the accountants of the Administration.